Pioneering the IBD specialist nurse role in China: a shared decision-making model for clinical practice innovation - Shuyan Li; Zijun Ni; Yan Ma; Yan Chen; Hongling Sun; Jingfen Jin; Jingfen Jin; Jingfen Jin (Frontiers in Medicine)
BackgroundInflammatory bowel disease (IBD) is a chronic condition characterized by the need for highly individualized treatment plans, requiring patients to make numerous complex medical decisions. Shared decision-making (SDM) has proven effective in improving treatment outcomes, patient satisfaction, and adherence in IBD management; however, its clinical implementation remains challenging. In China, formal SDM nurse roles have not yet been established.AimTo establish an IBD specialist nurse position to facilitate the effective implementation of SDM in IBD care, enhance patient engagement in disease management, and improve the overall quality of IBD care in China.MethodsSince March 2021, the Second Affiliated Hospital, School of Medicine, Zhejiang University has actively promoted the establishment of the IBD specialist nurse role. This initiative defined the organizational structure, selection criteria and processes, role functions, core competencies, and training and assessment standards for the position. Guided by the Ottawa decision support framework, the responsibilities of the IBD specialist nurse within the SDM model were clarified, offering new strategies and practical approaches for IBD patient management.ResultsBetween March 2021 and March 2024, the IBD specialist nurse managed 2,028 patient visits, including 1,352 cases of Crohn's disease and 676 cases of ulcerative colitis. These included patients who were newly diagnosed, perioperative, in the preconception stage or pregnant, receiving biological therapies, or requiring vaccinations. Decision conflict assessments in 121 perioperative patients demonstrated lower conflict levels compared to previous studies. “Annual team recognition” of the IBD nursing role reached 94.12%. Additionally, the IBD specialist nurse played a pivotal role in nursing discipline development by establishing clinical protocols, revising practice guidelines, enhancing patient education materials, and participating actively in quality improvement initiatives and research projects.ConclusionOur center successfully established the IBD specialist nurse role within the SDM framework, resulting in reduced patient decision conflict, improved treatment adherence, and enhanced quality of life. Future efforts will focus on refining the role evaluation system, optimizing training and promotion strategies, and strengthening policy support to further advance the professional development and broader implementation of IBD specialist nurses, thereby improving IBD management and healthcare delivery.